2023
DOI: 10.1007/s10103-023-03754-w
|View full text |Cite
|
Sign up to set email alerts
|

Laser acupuncture in the treatment of neuropathies in dentistry: a systematic review

Abstract: Laser acupuncture can be used to treat neurosensory alterations and motor disorders caused by dental treatments. This study aimed to review the existing literature on the effects of laser acupuncture on neuropathies in the context of dentistry and to search for treatment modalities in which this technique is used. This systematic review was conducted in accordance with the Cochrane Collaboration guidelines and the PICOS strategy. Randomized clinical trials that evaluated laser acupuncture as a primary interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Laser acupuncture involves irradiating acupoint skin with a low-intensity laser beam, producing various effects that penetrate deep into body tissues to treat diseases with anti-inflammatory and analgesic functions [ 114 , 115 ]. As a non-invasive, painless, safe, and effective method [ 116 , 117 ], laser acupuncture has been primarily used to treat neurological diseases [ 118 ], knee osteoarthritis [ 119 ], and functional constipation [ 120 ], but its application in treating PD remains limited. The scope of treatment with laser acupuncture and Mo still requires comprehensive and multi-level research.…”
Section: Discussionmentioning
confidence: 99%
“…Laser acupuncture involves irradiating acupoint skin with a low-intensity laser beam, producing various effects that penetrate deep into body tissues to treat diseases with anti-inflammatory and analgesic functions [ 114 , 115 ]. As a non-invasive, painless, safe, and effective method [ 116 , 117 ], laser acupuncture has been primarily used to treat neurological diseases [ 118 ], knee osteoarthritis [ 119 ], and functional constipation [ 120 ], but its application in treating PD remains limited. The scope of treatment with laser acupuncture and Mo still requires comprehensive and multi-level research.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is very few treatments for Bell’s palsy over 8 weeks other than recover naturally [ 1 ]. Acupuncture plays an important role in regulating “Qi and blood” in treating Bell’s Palsy, and the scientific mechanisms of acupuncture have been proven to be through multiple targets and multiple systems [ 20 , 31 , 32 ] and laser acupuncture and acupuncture show to have at least similar efficacy [ 33 – 35 ]. Therefore, our intervention included PBMT in affected side, and acupoints in abdomen, upper extremities and lower extremities in this study.…”
Section: Discussionmentioning
confidence: 99%
“…12 Other research examined laser acupuncture in the management of neurosensory alterations and motor disorders caused by dental treatment. 13 After a search of databases up to April 2022, 4 studies were identified. Risk of bias was included.…”
Section: Dentistrymentioning
confidence: 99%